Analysis of Factors Causing Delay in the Project of Installing Magnet Separators on the Barge Loading Conveyor (BLC) System - Nadia, Syahrani Sri; Hansen, Seng (President University, 2026)
Project delays frequently occur in industrial equipment installation projects and significantly affect time performance and contractual commitments. This research aims to identify the dominant factors causing delays in the magnet separator installation project on the Barge Loading Conveyor (BLC) system and to propose practical solutions to improve schedule performance. The research focuses on administrative and material procurement factors as well as manpower factors, in line with the project characteristics. A quantitative–descriptive method was applied using baseline schedule analysis, planned and actual S-curve comparison, weekly and cumulative progress deviation calculations, and Schedule Performance Index (SPI) analysis. The results were supported by interviews with project stakeholders. The findings reveal that delays in administrative processes and procurement approval of the main equipment significantly impacted the project because these activities were on the critical path. In addition, limited manpower competency reduced field productivity, resulting in cumulative schedule deviations with SPI values below 1. The research concludes that procurement and manpower are the most dominant delay factors and emphasizes the importance of preventive planning strategies, including clear project day zero determination, integrated procurement scheduling, competency-based workforce planning, and detailed milestone control.